Supraclavicular Brachial Plexus Block Guided by Ultrasonography in Pediatric Patient: A Case Report - I Made Dwi Pramana; Adinda Putra Pradhana (HM Publisher, 2023)
Background: Supraclavicular brachial plexus block has proven to be very useful in upper limb surgeries in pediatric patients. Supraclavicular brachial plexus block is preferred over general anesthesia for pediatric patients undergoing upper limb surgeries. This study aimed to report a procedure of supraclavicular brachial plexus block guided by ultrasonography in a pediatric patient undergoing orthopedic surgery on the upper extremity, which yielded good results, a high success rate, reduced opioid usage, and aided in faster recovery while minimizing complications. Case presentation: The patient was a 14-year-old child with a diagnosis of malunion in the left distal radius after open reduction internal fixation (ORIF) planned for osteoclasis surgery and ORIF with regional anesthesia through supraclavicular brachial plexus block. The patient was monitored during the surgery, and after the surgery, the patient returned to the ward; the patient was given oral analgesics without opioids for pain management. Conclusion: The efficient regional anesthesia procedure option for upper limb surgeries in pediatric patients is the supraclavicular brachial plexus block. Due to lower risks and fewer side effects, the supraclavicular brachial plexus block procedure is preferred over general anesthesia in pediatric patients.